PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PENYELENGGARAAN PELAYANAN BERBASIS ONLINE E-KTP DI DAERAH: (Studi Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Banyuasin) - Asmawati, Asmawati (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
One principle of good governance relates to good governance. Good governance means the use of state power in the performance of its tasks as a whole and as an activity unit organized as a whole in the economic, political and administrative spheres. The purpose of this study is to describe the principles of good governance in the implementation of Internet Electronic Indonesian Identity Card (E-KTP) services in the Population and Vital Statistics Office of Banyuasin Regency, and to describe the factors that support and prevent compliance. with principles. good governance in implementing E-KTP online services in Banyuasin Regency. The research used in this work is qualitative descriptive research, where the informants are the parties involved in the implementation of the E-KTP service. The data collection techniques used in this study were interviews, observation and documentation. The results of this study show that the implementation of the principles of good governance in the already working e-KTP services is in line with the prepared strategy. This study focuses on: 1) participation, 2) transparency, 3) accountability, and) rule of law. Some of the supporting factors include the decision of the head of Banyuasin Regency Population and Population Registration Office, ball collection and infrastructure. Public awareness of insufficient management of E-KTP and natural factors are factors that prevent the implementation of good governance principles in the implementation of online E-KTP services.